Proliferation Patterns in a Pig Model of AV Fistula Stenosis: Can we Translate Biology into Novel Therapies?. Issue 6 (28th May 2014) - Chan, Jenq‐Shyong; Campos, Begoña; Wang, Yang; Mistry, Meenakshi; Lee, Timmy; Munda, Rino; Arend, Lois; Roy‐Chaudhury, Prabir
Abstract Arteriovenous fistula (AVF) stenosis remains an important cause of AVF maturation failure for which there are currently no effective therapies. To understand the mechanisms involved, we have examined the pattern of cellular proliferation at different time points in a pig model of AVF stenosis. Immunohistochemical analysis of cellular proliferation was performed at 2, 7, 28, and 42 days. The distribution of cellular proliferation within the different layers of the vessel wall was also studied. An ANOVA analysis was used to identify differences between the magnitude of cellular proliferation at different time points and within different layers of the vessel wall. Adventitial proliferation occurred at 2 days and declined over time. Intimal and medial proliferation peaked at 7 days and then decreased over time. There was minimal proliferation in all three layers at the 28‐ and 42‐day time points. An important finding was the presence of active myofibroblast proliferation within "neointimal buds" at the 7‐day time point. Results suggest that there could be early adventitial activation, followed by a passage of these cells into the medial and intimal layers. These suggest that the application of perivascular antiproliferative (adventitial) therapies at the time of surgery could potentially reduce AVF maturation failure.